Work Stress and Its Association with Employee Performance: Evidence from the North Sumatra Provincial Health Office - Sri Lestari Ramadhani Nasution; Puji Lestari; Ermi Girsang (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Work-related stress is a growing concern in public institutions, particularly in health departments where employees often face complex administrative tasks, urgent program execution, and public accountability pressures. This study aims to examine the relationship between work stress and employee performance at the Health Department of North Sumatra Province in 2025. Using a quantitative cross-sectional design, the study involved 300 employees selected through total sampling. Data were collected via structured questionnaires measuring four dimensions of work stress-task demands, role demands, organizational structure, and organizational leadership-and their association with employee performance. Chi-square tests and binary logistic regression were used for analysis. The results revealed that task demands, organizational structure, and leadership showed significant associations with performance, while role demands did not. In multivariate analysis, organizational leadership emerged as the most influential factor (Exp(B) = 2.470; 95% CI = 1.535-3.975), followed closely by organizational structure (Exp(B) = 2.345; 95% CI = 1.458-3.773). These findings indicate that employees who perceive strong leadership and well-defined organizational systems are significantly more likely to perform well. The results also suggest that unclear structures and rigid bureaucratic leadership styles may hinder performance. This study underscores the importance of organizational reforms that prioritize leadership development, structural clarity, and stress management strategies. It provides valuable empirical evidence for policymakers and health administrators to formulate targeted interventions that enhance employee well-being and institutional effectiveness in Indonesia's public health sector. Keywords: Work-Related Stress, Employee Performance, Organizational Leadership, Public Health Sector, Organizational Structure.